The creaky knees guide, Oregon : the 85 best easy hikes - Blair, Seabury (Sasquatch Books, 2022)
"The updated edition of this bestselling guide (25,000 copies sold) features 85 of the best low-impact day hikes in Oregon state, perfect for aging baby boomers, seniors, those traveling with small children, and anyone else interested more in a stroll than a climb. The Creaky Knees Guide Oregon is a day-hiking guidebook filled with kinder, gentler trails, featuring the best easy-to-walk hikes throughout the state. Written in an informative style that will appeal to anyone, regardless of age, the guide covers hikes in six regions throughout the state, including the Oregon Coast, Columbia River Gorge, and Mount Hood. There is also a section on urban hikes and walks. Each trail description includes elevation gains, including a topographical map; clear, up-to-date driving directions; mileage and estimated hiking time; trail conditions; and more."--Publisher.